OPTIMIZING ELDERLY HEALTH THROUGH NUTRITIONAL COUNSELING EFFORTS AND EARLY DETECTION: OPTIMALISASI KESEHATAN LANSIA MELALUI UPAYA PENYULUHAN ZAT GIZI DAN DETEKSI DINI - Rindayati; Abd Nasir; Susilo Harianto; Emuliana Sulpat; Hafna Ilmy Muhalla; Sofiatun (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Elderly are susceptible to various health problems, where one aspect that greatly influences the health of the elderly is the fulfillment of proper nutritional needs. Objective: This activity aims to increase knowledge about optimizing the health of the elderly through nutritional counseling and early detection status. Method: The method used is to provide counseling through lectures and then discussion sessions. The evaluation of this activity using a pre-test and post-test were carried out 10 questions with a score of 10 for each question. The total score was averaged to obtain the mean score. Early detection through measuring body weight, cholesterol levels, blood sugar and uric acid to determine the health problems of the elderly. Results: The results of the activity were that the elderly who attended 76 people experienced an increase in knowledge about nutrients, from the answers to questions given to 15 counseling participants. Health checks found values above normal, namely 7 people's weight, 9 people's blood pressure, 6 people's blood sugar, 8 people's cholesterol, and 5 people's uric acid, while values below normal were 4 people's weight. This activity also increased participants' knowledge from an average pretest score of 56 to a post-test of 85. Conclusion: Nutrition counseling and health checks have the potential to have a positive impact on the health and quality of life of the elderly. The importance of nutritional education and early detection of elderly health problems so that the quality of life of the elderly is maintained.